أثر قدرة قراءة القرآن في سيطرة النطق بالكلمات العربية لدي اللطالبات بمعهد زينة العلوم الدينية الإسلامية مولابوه - Danial Jamal; Saflika Aprilia (Yayasan Sagita Akademia Maju, 2026)
This study aims to examine the relationship between students’ ability to read the Qur’an and their ability to pronounce Arabic words accurately. The study is motivated by the observation that some students continue to experience difficulties in Arabic pronunciation despite having received formal instruction in the language. It is based on the assumption that Qur’anic reading, which requires precision in articulation points and phonetic features of letters, can contribute to the improvement of phonetic skills in Arabic language learning. This research employed a field research method with a quantitative approach. The sample consisted of 20 female students. Data were collected through observation and interviews, as well as tests of Qur’anic reading ability and Arabic word pronunciation. The data were analyzed using Pearson’s correlation coefficient. The findings indicate a statistically significant effect between the ability to read the Qur’an and the ability to pronounce Arabic words, with a correlation coefficient of (r = 0.90), suggesting a strong relationship between the two variables. The study concludes that regular engagement in Qur’anic reading not only has religious significance but also plays an effective role in developing phonetic skills in Arabic language learning.